"Double Door" Opening of the Japan Sea Inferred by Pn Attenuation Tomography. Issue 16 (16th August 2022) - Yang, Geng; Zhao, Lian‐Feng; Xie, Xiao‐Bi; He, Xi; Lü, Yan; Yao, Zhen‐Xing
Abstract: The extension of back‐arc basins and formation of marginal seas following the subduction of oceanic lithosphere are usually attributed to the rollback of subducting slabs and distorted mantle convection. However, for the Japan Sea, the largest marginal sea in the northwestern Pacific, its opening is unlikely only resulted from the subduction of the Pacific plate because of the coeval Philippine plate subduction and the arcuate arc volcanic zone. Therefore, the present‐day thermal structure in the uppermost mantle, which can be directly constrained by strong Pn‐wave attenuation, plays a vital role in understanding the Japan Sea opening. Here, we observe two belts of strong Pn attenuation beneath the Japan Sea; their strikes are generally consistent with local Pn anisotropy and the retreat directions of the Pacific and Philippine trenches. Hence, there seem to be two divergent mantle flows in the uppermost mantle, pushing a "double door" for the Japan Sea opening. Plain Language Summary: The western Pacific is one of the most active regions of global tectonics. For the Japan Sea, the largest marginal sea in the northwest Pacific, its formation mechanism is still controversial. The Japan Sea may have experienced a complex evolution process driven by the superposition of multiple mechanisms, and finally produced a diamond‐shaped ocean. The present thermal structure in the uppermost mantle, which can be directly constrained by strong Pn‐wave attenuation, plays a vital role in understanding the Japan Sea opening. In this study, we construct a high‐resolution broadband Pn attenuation model for the uppermost mantle beneath the Japan Sea. Two strong Pn attenuation belts are observed in this region, with their strikes generally consistent with the local Pn velocity anisotropy and the opening directions of the Japan Sea. Therefore, two divergent mantle flows likely exist in the uppermost mantle, pushing the opening of the Japan Sea like a "double door." These mantle flows could be part of mantle convection in a big mantle wedge, where ascending hot materials from the deep mantle not only feed volcanoes in northeastern Asia but also thicken the back‐arc oceanic crust. Key Points: A high‐resolution broadband Pn attenuation model is obtained beneath the Japan Sea Hot mantle materials ascend to feed the volcanoes in NE Asia, intruding into and thickening the oceanic crust in the Japan Sea Divergent mantle flows likely push the fan‐shaped rotational opening of the Japan Sea